THE RE-MYTHOLOGIZATION AND THE ROLE OF RE-MYTHOLOGIZATION IN SOCIETY - Usmanov Muxriddin Abdimuratovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article analyzes the factors associated with the emergence of myth in today’s society, and the formation of the mythological worldview. Also it discussed aspects of myths related to social life, focusing on myths that reflect reality. Mechanisms of re mythologization are explained on the basis of ontological and epistemological knowledge.